SHOULD WE OFFER OPPORTUNISTIC VACCINATION IN THE PAEDIATRIC EMERGENCY DEPARTMENT?. Issue 12 (23rd November 2015) - Newell, K; Rousseva, C; Slade, C; Isba, R
Abstract : Objectives & Background: Despite the importance of children being up-to-date with routine childhood immunisations, uptake rates remain sub-optimal. Guidance from NICE and the WHO state that every contact a child has with healthcare services be thought of as an opportunity to provide catch-up immunisation. Paediatric emergency departments (PED) therefore have the potential to increase local vaccination rates. The overall aim of this work was to look at the viability of introducing opportunistic vaccination into the PED. The aim of these two audits was to look at potential barriers to such a programme. Audit 1: is vaccination status recorded in the notes of children presenting to the PED at North Manchester General Hospital (NMGH)? Audit 2: do PED staff currently deliver vaccinations in the department? Methods: Audit 1: a retrospective audit of the notes of 500 children who presented to the PED before their third birthday. Basic demographic data were recorded along with what vaccination history appeared in their notes. Audit 2: a retrospective audit of pharmacy orders for vaccines for the PED over a five and a half year period. These data were used as a proxy for how many vaccinations were administered in the PED the same time period. Results: The audit of vaccination status demonstrated that only 28% of attendees had their vaccination status recorded, but 93% of these were up-to-date with their vaccinations to an age-appropriate level. The audit of paediatric vaccinations demonstrated that across the 66 month period, 75 vaccinations were ordered. This work suggests vaccination status is not well recorded in the PED. In the absence of access to centrally-held vaccination records, this may prevent introduction of a successful programme. Additionally, it appears that only a small number of vaccinations are currently given in the department, suggesting that there may not be sufficient existing vaccination expertise. Conclusion: Whilst these findings do not support the introduction of opportunistic vaccination to provide catch-up for routine childhood immunisations, this approach deserves further exploration and future work could look at signposting children back to primary care, rather than offering the vaccination in the department. However, it may be possible to offer other, non-routine vaccines in the PED as a way to increase local vaccination rates e.g. by offering intranasal seasonal influenza vaccination to children attending the PED.